Privacy and Confidentiality in Blockchain Systems: Investigating Privacy-Enhancing Techniques and Confidentiality Mechanisms in Blockchain Systems (Blockchain Technology and Distributed Systems, 2023)
Blockchain technology has revolutionized various industries by providing decentralized and transparent systems. However, privacy and confidentiality remain critical challenges in blockchain systems, as transactions are publicly recorded. This paper investigates privacy-enhancing techniques and confidentiality mechanisms in blockchain systems, focusing on zero-knowledge proofs, ring signatures, and homomorphic encryption. We evaluate the effectiveness of these techniques in protecting user privacy and ensuring data confidentiality, discussing their advantages, limitations, and real-world applications. Additionally, we explore challenges and future research directions in enhancing privacy and confidentiality in blockchain systems.
Keywords: blockchain; privacy; confidentiality; zero-knowledge proofs; ring signatures; homomorphic encryption; data protection; decentralized systems; cryptography